Hubungan Kualitas Pelayanan dan Lokasi dengan Loyalitas Pelanggan di Raihan Bakery Cake & Shop Medan - Fitri Dwi Setya; M. Rajab Lubis; Sjahril Effendy (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2020)
This study aims to determine the relationship between service quality and location variables with customer loyalty at Raihan Bakery Cake Shop Medan. The population in this study was as much 2100 taken from customers who are truly loyal to Raihan Bakery Cake Shop Field. This research uses a quantitative approach and sampling in this study with purposive sampling technique amounted to 100 people. The instrument used was a valid and reliable questionnaire for service quality, location and customer loyalty. The research was analyzed using the Multiple Analysis test. The results showed that: (1) There is a positive relationship Rx1-y = 0.0446 of service quality with customer loyalty at Raihan Bakery Cake Shop Medan. This is indicated by tcount = 4,938 ttable = 1,985 and a significance value of 0,000 0.05. (2) There is a positive relationship Rx2-y = 0.172 from the location with customer loyalty at Raihan Bakery Cake Shop Medan. This is indicated by tcount = 1,731 ttable = 1.985 and a significance value of 0.043 0.05. (3) There is a positive relationship Rx1.x2-y = 0.0448 of service quality and location with customer loyalty at Raihan Bakery Cake Shop Medan. And from the output obtained a determinant coefficient (R2) of 0.200 with a significance value of 0.000 0.05.